2005
DOI: 10.1143/jjap.44.3879
|View full text |Cite
|
Sign up to set email alerts
|

Low-k SiOCH Film Deposited by Plasma-Enhanced Chemical Vapor Deposition Using Hexamethyldisiloxane and Water Vapor

Abstract: We have developed low dielectric constant SiOCH films by plasma-enhanced chemical vapor deposition (PE-CVD) using hexamethyldisiloxane (HMDSO) containing a siloxane structure and water vapor (H2O) gases. Although the film was deposited using H2O vapor, the content of H2O is very small and the k value can be reduced to the order of 2.5. The leakage current is small and on the order of 10-9 to 10-10 A/cm2 at 1 MV/cm2. The hardness and Young's modulus are larger than 2 and 10 GPa, respectively at the k value of 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 11 publications
0
16
0
Order By: Relevance
“…The peaks are characteristic for alkyl-substituted polysiloxane PP-films. 16,[35][36][37] The most remarkable difference between the two spectra is associated with the peak at 2966 cm -1 . As seen in the inset, the intensity of this peak relative to the Si-O peak is lower for the annealed film, indicating partial elimination of hydrocarbons present in the as-deposited film upon annealing at 600 °C.…”
Section: Resultsmentioning
confidence: 96%
“…The peaks are characteristic for alkyl-substituted polysiloxane PP-films. 16,[35][36][37] The most remarkable difference between the two spectra is associated with the peak at 2966 cm -1 . As seen in the inset, the intensity of this peak relative to the Si-O peak is lower for the annealed film, indicating partial elimination of hydrocarbons present in the as-deposited film upon annealing at 600 °C.…”
Section: Resultsmentioning
confidence: 96%
“…The density was calculated using the electron density measured from the critical angle of X-ray total reflection and the composition. H concentration is estimated to be 40% (shown in [1]) and this value is employed in density calculation. The result is shown in Fig.…”
Section: Densitymentioning
confidence: 99%
“…The dielectric constant of PE-CVD low-k film can be reduced by introducing CH 3 bonds into the film and forming small pores. However, it is well known that the mechanical strength of PE-CVD low-k film abruptly declines at smaller k value than 2.7 [1]. The film with k value smaller than 2.7 cannot withstand chemical mechanical polishing (CMP) process for planarizing interlayer dielectric films.…”
Section: Introductionmentioning
confidence: 99%
“…Similar results were reported by Borvon et al [13] except that they admixed methane to a HMDSO-O 2 gas mixture. Shioya et al [14] also reported low-k dielectric films, but they used HMDSO admixed with water vapor. Gengenbach et al [15] also used hexamethyldisilazane (HMDSA) apart from HMDSO and studied the ageing mechanisms stressing the post-deposition kinetics.…”
Section: Introductionmentioning
confidence: 99%